2018
DOI: 10.1016/j.pcd.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The identification of higher forefoot temperatures associated with peripheral arterial disease in type 2 diabetes mellitus as detected by thermography

Abstract: Contrary to expectations the mean toe and forefoot temperatures in DM patients with PAD is higher than in those with DM only. This unexpected result could be attributed to disruption of noradrenergic vasoconstrictor thermoregulatory mechanisms with resulting increased flow through cutaneous vessels and subsequent increased heat emissivity. These results demonstrate that thermography may have potential in detecting PAD and associated temperature differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…Perhaps if the limb elevation was maintained for a longer period of time, the vascular changes would have been sufficient to cause a change in temperature that could have been detected by the sensitive thermal camera. As in our previous studies [9,10], but in contrast with other works [6,7], again patients with PAD exhibited higher foot temperatures. Based on our results, higher temperatures are recorded in PAD, and therefore this may be used as a potential diagnostic tool.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Perhaps if the limb elevation was maintained for a longer period of time, the vascular changes would have been sufficient to cause a change in temperature that could have been detected by the sensitive thermal camera. As in our previous studies [9,10], but in contrast with other works [6,7], again patients with PAD exhibited higher foot temperatures. Based on our results, higher temperatures are recorded in PAD, and therefore this may be used as a potential diagnostic tool.…”
Section: Discussionsupporting
confidence: 70%
“…A number of studies have shown that there is a decrease in cutaneous temperatures of the foot in patients with PAD when compared to patients without PAD [6][7][8]. In contrast, Gatt et al [9,10] have shown that, somewhat surprisingly, PAD in diabetes presents with higher temperatures similar to the other complications of this disease, including neuropathy and neuroischaemia. Notwithstanding the fact that baseline thermographic data of healthy adults exists [11], together with data of persons with diabetes, PAD and neuropathy, medical thermography, with its advantages of non-invasive and non-contact assessment of radiating temperature, is still not an accepted clinical tool for the identification of these conditions, apart from the identification of unilateral disease processes which can be compared to the unaffected foot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 Hand temperature distribution 16 and foot thermal distribution were used to identify peripheral arterial disease. 17 , 18 Differences between peripheral organs (ears) and core body temperature 19 and thermal gradient along the arm 20 were used for shock diagnosis.…”
Section: Technologies and Challengesmentioning
confidence: 99%